2020
DOI: 10.1177/2055217320974388
|View full text |Cite
|
Sign up to set email alerts
|

EMDR treatment for anxiety in MS patients: A pilot study

Abstract: Background Patients with multiple sclerosis (MS) often experience high levels of anxiety, specifically about the (unpredictable) future related to MS. Worries about physical and cognitive declines can cause frightening mental representations of future ‘worst-case scenarios’. Evidence of the applicability of eye movement desensitization reprocessing (EMDR) using flash-forward on anxiety is growing. Objective This pilot study examines the flash-forward EMDR procedure as a treatment option in MS patients sufferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…(Ahmed, 2018 ; Amano & Toichi, 2017 ; van der Wielen et al, 2019 ) (Carletto et al, 2016 ; Wallis & de Vries, 2020 ) (Guina & Guina, 2018 ; Janssen & van Donzel, 2023 ; Smart, 2022 ) (Hatefi et al, 2019 ; Olędzka et al, 2016 ) (Konuk et al, 2011 ) (Chemali & Meadows, 2004 ) (Gil-Jardine et al, 2018 ) (Gattinara, 2009 ) See Supplementary Table 4B. The efficacy of EMDR (Gattinara, 2009 ; Olędzka et al, 2016 ; van der Wielen et al, 2019 ) (Carletto et al, 2016 ; Wallis & de Vries, 2020 ) (Ahmed, 2018 ; Arabia et al, 2011 ; Carletto et al, 2016 ; Guina & Guina, 2018 ; Hatefi et al, 2019 ; Olędzka et al, 2016 ; Smart, 2022 ; van der Wielen et al, 2019 ; Wallis & de Vries, 2020 ) (Ahmed, 2018 ; Carletto et al, 2016 ; Hatefi et al, 2019 ; Smart, 2022 ; van der Wielen et al, 2019 ; Wallis & de Vries, 2020 ) (Wallis & de Vries, 2020 ) (Wallis & de Vries, 2020 ) (Carletto et al, 2016 ; Gil-Jardine et al, 2018 ; Janssen & van Donzel, 2023 ; Smart, 2022 ) (Janssen & van Donzel, 2023 ) (Smart, 2022 ) (Amano & Toichi, 2017 ; Carletto et al, 2016 ; Chemali & Meadows, 2004 ; Gil-Jardine et al, 2018 ; Konuk et al, 2011 ; Olędzka et al, 2016 ) (van der Wielen et al, …”
Section: Resultsunclassified
“…(Ahmed, 2018 ; Amano & Toichi, 2017 ; van der Wielen et al, 2019 ) (Carletto et al, 2016 ; Wallis & de Vries, 2020 ) (Guina & Guina, 2018 ; Janssen & van Donzel, 2023 ; Smart, 2022 ) (Hatefi et al, 2019 ; Olędzka et al, 2016 ) (Konuk et al, 2011 ) (Chemali & Meadows, 2004 ) (Gil-Jardine et al, 2018 ) (Gattinara, 2009 ) See Supplementary Table 4B. The efficacy of EMDR (Gattinara, 2009 ; Olędzka et al, 2016 ; van der Wielen et al, 2019 ) (Carletto et al, 2016 ; Wallis & de Vries, 2020 ) (Ahmed, 2018 ; Arabia et al, 2011 ; Carletto et al, 2016 ; Guina & Guina, 2018 ; Hatefi et al, 2019 ; Olędzka et al, 2016 ; Smart, 2022 ; van der Wielen et al, 2019 ; Wallis & de Vries, 2020 ) (Ahmed, 2018 ; Carletto et al, 2016 ; Hatefi et al, 2019 ; Smart, 2022 ; van der Wielen et al, 2019 ; Wallis & de Vries, 2020 ) (Wallis & de Vries, 2020 ) (Wallis & de Vries, 2020 ) (Carletto et al, 2016 ; Gil-Jardine et al, 2018 ; Janssen & van Donzel, 2023 ; Smart, 2022 ) (Janssen & van Donzel, 2023 ) (Smart, 2022 ) (Amano & Toichi, 2017 ; Carletto et al, 2016 ; Chemali & Meadows, 2004 ; Gil-Jardine et al, 2018 ; Konuk et al, 2011 ; Olędzka et al, 2016 ) (van der Wielen et al, …”
Section: Resultsunclassified
“…Another study that concluded of Major enhancement was exposed after (EMDR) treatment compared to before (EMDR) treatment on anxiety, depression, and worry. But the management of Anxiety by EMDR approach need to conducting further research studies (Wallis & de Vries, 2020).…”
Section: Standardization Of Emdr-based Intervention Protocolmentioning
confidence: 99%
“…27,30 The remaining pilot RCT compared an EMDR standard protocol to an EMDR pain protocol and control psychotherapy and found beneficial effects of both EMDR protocols over control therapy, in favor of the standard protocol which was found to be significantly better compared to the pain protocol. 32 Neurology 15 studies described the efficacy of EMDR in neurological disorders and focused on patients suffering from: dementia, [34][35][36] multiple sclerosis (MS), 37,38 stroke, [39][40][41] amyotrophic lateral sclerosis (ALS), 42 spinal cord injury, 43,44 migraine, 45 psychogenic seizures, 46 and concussion-like symptoms. 47 One study did not specify which neurological condition the patients suffered from.…”
Section: Main Findings Per Medical Domain Painmentioning
confidence: 99%
“…48 See Supplementary Table 4B. The efficacy of EMDR was evaluated on emotional distress, 36,44,48 QoL, 37,38 and symptoms of depression, 34,[36][37][38][39]41,43,44 anxiety, 34,[36][37][38]41,43 worry, 38 cognitive avoidance, 38 and PTSD, 37,40,41,47 self-esteem, 40 and post-traumatic growth. 41 Additionally, multiple studies focused on treating symptoms of specific disorders, 35,37,[44][45][46][47] e.g., fatigue in patients with MS. All studies reported beneficial effects of EMDR when comparing measurements before and after treatment, except for one case study: the study reported that the symptoms of anxiety and depression remained consistent although the patient, suffering from Alzheimer's disease, subjectively reported less distress.…”
Section: Main Findings Per Medical Domain Painmentioning
confidence: 99%